Principles and Practice of Non Life Insurance. - Gupta, P. K. (Himalaya Pub. House, 2009)
The book has been divided into specific units which respectively cover insurance and risk management basics, pricing, underwriting and legal aspects, life and non-life insurance-concepts and procedures. Overall, the book presents an emerging dimension of insurance and risk management, especially in Indian context. This book is an attempt to conceptualise the students with fundamental principles of non-life insurance also provide an in-depth knowledge on the practice of non-life insurance.